Hyperregenerative macrocytic anaemia: the role of copper and zinc. Issue 4 (14th April 2021) - Hofmann, Patrick; Buetikofer, Claudia; Bächli, Esther
Abstract : In a patient with a history of bariatric surgery, severe copper deficiency presenting with macrocytic hyperregenerative anaemia was diagnosed. Besides the impaired intestinal absorption due to a short bowel syndrome, the enteral zinc supplementation competitively decreased the intestinal copper uptake. Once the zinc supplementation was stopped, enteral copper replacement ensued and normalised haemoglobin levels with decreasing median corpuscular volume were observed during follow-up visits.